Strengthening of Human Resources Quality and in Managerial Capacity Teacher Competence Improvement in Labuhan Batu Selatan District - Zuhri Aulia; Pristiyono Pristiyono; Pitriyani Pitriyani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Student Worksheet (LKPD) is a supporting tool as a tool to A teacher who takes a student-to-student approach also requires expertise in leading a class so that a learning process is created in accordance with existing rules. This is called the quality of human resources and managerial abilities. The type of research used in this research is quantitative research. The population in this study was 3094 people and the sample used was selected using the slovin formula with a total of 100 people. The data analysis method used in this study is component or variance based structural equation modeling where the data processing uses Partial Least Square (Smart-PLS) version 3.0. The results of the study stated that the quality of human resources obtained a T-statistic value of 3.338> 1.96 with a P-value of 0.001. This means that the quality of human resources has a significant effect on competence, or H1 is accepted. Then managerial ability obtains a T-statistic value of 4.559 <1.96 with a P-value of 0.210. This means that managerial ability has a significant effect on competence, or H2 is accepted.